ANALISIS BEBAN KERJA KARYAWAN DIVISI BISNIS PT BPRS HARTA INSAN KARIMAH MITRA CAHAYA INDONESIA - Rio Dewangga; Suci Utami Wikaningtyas; Insiatiningsih Insiatiningsih (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study aims to evaluate the physical and mental work load of employees in the business division of PT Bank Pembiayaan Rakyat Syariah Harta Insan Karimah Mitra Cahaya Indonesia PT BPRS HIK MCI. The background of this study stems from indications of an uneven workload among employees, which can disrupt team productivity and effectiveness. The method used in this study is a qualitative descriptive approach with data collection techniques through questionnaires, observations, and interviews to obtain a complete picture of the employees' workload. The analysis of physical workload was conducted using the Work Load Analysis WLA method, while mental workload was evaluated using the National Aeronautics and Space Administration-Task Load Index NASA TLX. The results of the physical workload measurement of employees in the business division of PT BPRS HIK MCI showed that it was indeed uneven but did not cause a significant gap between employees. The mental workload conditions were relatively uniform, with the average mental workload being moderately high to high. It is hoped that the results of this study can reveal the actual workload levels, identify the factors causing the unevenness, and provide recommendations for solutions to the workload issues. This research is expected to provide theoretical benefits for the development of the concept of workload analysis and also serve as a basis for the management of PT BPRS HIK MCI in formulating more effective, fair, and sustainable human resource strategies.